PJMHS 2021
DOI: 10.53350/pjmhs211561773
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation the effect of progressive muscle relaxation technique on fatigue and daily living activities in patients with Multiple Sclerosis

Abstract: Aim: This is a Quasi-experimental study wich was carried out in order to determine the effects of applying progressive muscle relaxation on fatigue and daily living activity of MS patients. Background: Fatigue is one of the most common symptoms in people with multiple sclerosis (MS) and adversely affects their daily living activities. Methods: 80 MS Patients were selected then conducted in two group (40 experiments and 40 contorol). Data collector tools included: demographic questionnaire, fatigue severity sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…Between-group comparisons varied: in three studies, active comparisons were associated with greater gains than relaxation, however mean fatigue severity scores were also lower with relaxation compared to usual care 19 or no treatment. 49,50…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Between-group comparisons varied: in three studies, active comparisons were associated with greater gains than relaxation, however mean fatigue severity scores were also lower with relaxation compared to usual care 19 or no treatment. 49,50…”
Section: Resultsmentioning
confidence: 99%
“…Between-group comparisons varied: in three studies, active comparisons were associated with greater gains than relaxation, however mean fatigue severity scores were also lower with relaxation compared to usual care 19 or no treatment. 49,50 In one study, participants who underwent multidisciplinary rehabilitation had better energy conservation strategies compared with those who underwent progressive muscle relaxation at 16-week-follow-up. 37 An additional five studies reported non-significant group effects for fatigue, regardless of the control condition.…”
Section: Fatiguementioning
confidence: 99%
“…Javdan ve ark. (38) tarafından Multipl Skleroz hastalarında (n=80) yürüttükleri yarı deneysel çalışmada, progresif gevşeme egzersizlerinin yorgunluk ve günlük yaşam aktiviteleri üzerine etkisini değerlendirmişlerdir. Deney grubuna (n=40) 8 hafta boyunca günde birer kez PGE uygulanmıştır.…”
Section: Progresif Gevşeme Egzersizlerinin Yorgunluk üZerine Etkileriunclassified